PENGARUH EKSPEKTASI RETURN, SELF EFFICACY, RISIKO, TEKNOLOGI, DAN PELATIHAN PASAR MODAL TERHADAP MINAT INVESTASI(Studi kasus Pada Investor Phintraco Sekuritas Di Universitas Halu Oleo) - Faisal Maarif; Dedy Takdir Syaifuddin; Salma Saleh; Sujono Sujono; Nuryamin Budi (Jurnal Manajemen dan Kewirausahaan, 2023)
The purpose of this study was to determine the effect of return expectations, self-efficacy, risk, technology, and capital market training on investment intentions. The population in this study were Phintraco Securities Investors at Halu Oleo University, totaling 105 people as the research sample. The research sample was selected using probability sampling technique. The research data is primary data. The analysis technique used is multiple linear analysis with the help of the SPSS version 26 program.The results of this study are: (1) Expected return has a positive and significant effect on investment intention, (2) self-efficacy has a positive and significant effect on investment intention, (3) risk has a positive and significant effect on investment intention. intention, (4) technology has a positive and significant effect on investment interest, (5) capital market training has a positive and significant effect on investment interest, (6) Expected Return, Self Efficacy, Risk, Technology, and Capital Market Training simultaneously have a significant positive effect to Investment Interest.